The Technical Development of Traction Inverter for Urban Rail Transit Vehicle - 翁星方; 邹档兵 (机车电传动)
First of all, the development of traction inverter and power circuit were introduced simply. Secondly, the simplified traction inverter with completely independent intellectual property rights was analyzed. Finally, the radiator of traction inverter and the IGBT converter module were introduced in detail. The simplified traction inverter was proved satisfying the demand of urban rail transit vehicle traction system.